Electroencephalography Alpha Spectral Characteristics in the Parieto-Occipital Lobe of Elderly Patients with Chronic Insomnia and Mild Cognitive Impairment - GUO Zhenxing; BAI Linxin; ZHANG Lin; GAO Jiahui; RAO Ting; LIU Zhizhen (康复学报)
ObjectiveTo analyze the electroencephalography (EEG) alpha spectral characteristics in the parieto-occipital lobe of elderly individuals with chronic insomnia and mild cognitive impairment (MCI).MethodsA total of 80 elderly individuals from the Gudong and Wenquan communities in Fuzhou, Fujian Province were recruited from June 2019 to December 2020, including 30 cases in the healthy control group (HC), 20 cases in the chronic insomnia (CI) group and 30 cases in the CI combined with MCI (CI-MCI) group. The Pittsburgh sleep quality index (PSQI) was used to assess sleep quality; Fuzhou version of the Montreal cognitive assessment (MoCA) was used to evaluate cognitive functions (visuospatial execution, naming, attention, verbal fluency, abstraction, delayed recall and orientation). Neuroscan 64-channel EEG instrument synchronous EEG recording system was used to collect daytime resting-state EEG signals, and the differences and changing trends of alpha (8-13 Hz) power values of each channel in parieto-occipital lobe were compared.The correlation between the change of alpha spectral power in the parieto-occipital lobe and cognitive function was analyzed.Results(1) PSQI scores: compared with the HC group, the daytime functional impairment scores in the CI-MCI group were significantly higher, with a statistically significant difference (P<0.05). The total PSQI scores, sleep quality, sleep onset latency, total sleep time, sleep efficiency and sleep disturbance scores in both the CI group and the CI-MCI group were significantly higher, while the use of hypnotics scores were significantly lower, and the differences were statistically significant (P<0.05).(2) MoCA scores: compared with the HC group and the CI group, total MoCA score, and the scores of visuospatial execution, naming, attention, verbal fluency, abstract abilitivies, delayed recall and orientation in the CI-MCI group were significantly lower, and the differences were statistically significant (P<0.05).(3) EEG spectral characteristics: compared with the HC group, P1, P6, POZ, PO4, PO6 alpha spectral power of parieto-occipital lobe in the CI-MCI group increased significantly (P<0.05). Compared with the HC group, alpha spectral topography of parieto-occipital lobe in the CI-MCI group showed stronger spectral power. (4) Correlation between changes in parieto-occipital alpha spectral power and cognitive function: the alpha spectral power at site P6 in the right parietal lobe (r=0.444, P=0.023), at site POZ in the parieto-occipital lobe (r=0.444, P=0.023), and at site PO4 in the right parieto-occipital lobe (r=0.478, P=0.014) all showed a positive correlation with visuospatial executive function.ConclusionThe change of alpha spectral power of parieto-occipital lobe is the manifestation of cognitive impairment in the elderly with chronic insomnia and MCI. The alpha spectral power of parieto-occipital lobe can regulate the cognitive function of the elderly with chronic insomnia and MCI.